Cardiac SPECT imaging - DePuey, E. Gordon; Garcia, Ernest V; Berman, Daniel S (Lippincott Williams & Wilkins, 2001)
Columbia Univ., New York, NY. Reference for physicians referring patients for diagnostic imaging and should also benefit technologists and basic scientists. Technical advances and the clinical role of cardiac SPECT are highlighted. Includes halftone illustrations. Previous edition: c1995. DNLM: Heart--radionuclide imaging.
Keywords: Heart; srdce; angiologie; kardiologie